Effectiveness of YouTube Videos in Learning Database Courses among University Students - Nasaruddin, Nor Intan Shafini; Awang, Norbahiyah (Information Management and Business Review, 2024)
This research explores the effectiveness of YouTube videos as supplementary resources for students studying database subjects. With the growing use of digital media in education, it is vital to understand how these resources impact learning outcomes. Using a mixed-methods approach, the study collects quantitative data through surveys and qualitative insights through interviews. The results indicate that YouTube videos significantly improve students’ understanding, engagement, and retention of database concepts. The study concludes with recommendations for educators on effectively incorporating YouTube into their teaching strategies. This paper investigates the effectiveness of YouTube videos as a learning tool for students studying database subjects. With the increasing availability of online resources, it is essential to evaluate how these resources impact student learning outcomes. The study utilizes a mixed-methods approach, combining quantitative data from surveys and qualitative data from interviews with students. The findings suggest that YouTube videos enhance understanding, engagement, and retention of database concepts, while also providing flexibility and accessibility. Recommendations for educators on integrating YouTube into curriculum design are discussed.